The Role of Synovial Biomolecules Nano-Tribology in the Articulation Between Artificial Joint Materials - Yang, Charng-Bin; Huang, Huei-Ting; Chen, Chia-Chun; Lai, Yu-Hsun; Huang, Chung-Hsiung; Lu, Yung- Chang; Fang, Hsu-Wei (Current Nanoscience, 2014)
Ultra-high molecular weight polyethylene (UHMWPE) wear debris induces osteolysis and leads to the loosening or failure of artificial joint. The lifetime of artificial joint is mainly determined by its tribological behaviors in synovial fluid. Various synovial fluid compositions such as albumin, globulin, hyaluronic acid (HA) and phospholipid might influence the tribological performance. Therefore, we investigated the nano-tribological behaviors of different biomolecules in synovial fluid for improving the lubrication of artificial joint. In this study, a biomimetic synovial fluid was used as baseline to examine the tribological effects of adding various biomolecules to synovial fluid. The results indicated that adding HA molecules to synovial fluid reduced the friction coefficient and increased the viscosity. Moreover, HA had the potential to decrease the friction caused by accumulative albumin and γ-globulin in synovial fluid. In summary, the findings demonstrated that HA was a critical synovial fluid molecule in dominating the lubricating properties of artificial joint. The efficient concentration of HA in synovial fluid could be adjusted to 4.5 mg/ml. The role of biomolecules in dominating the nanotribological process of artificial joint materials was investigated in this study. It was thought the nano-scaled interactions between the biomolecules may construct the major mechanisms.
Keywords: lubrication